Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1021/j100353a004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast temperature jump studies of hydrogen bonds

Abstract: HCO+v, 430 (100) 751" 890d "Reference 10. 6Reference 11. "Reference 12. ''Reference 13. excitation are expected. Since hot bands have not been observed for HCO+, its Tv has been assumed to be the same as that observed for HN2+; this assumption is supported by the similarity in their measured rotational temperatures and in their vibrational frequencies. From the 7r and 7V measurements, Zr~' and Zv"* were calculated by using the standard equations8 and used to determine R¡f, and subsequently Sv°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The equilibrium constant in the ground state has been estimated to be 1.86 and the hydrogen-bond formation time and the lifetime of hydrogen bond have been determined to be 65 and 120 ps, respectively. The lifetime is similar to the reported 250 ps lifetime of hydrogen bonds in ethanol oligomers isolated in a non-polar solvent [109], but is much longer than the subpicosecond lifetime reported in pure water [110]. The lack of a strong viscosity dependence of the equilibration time suggested that the bond formation/breaking event was a very local motion that did not involve motion of the center of mass of the solvent molecule or largescale rearrangement of the solvent hydrogen-bond network but, rather, that only a simple rotation around the O--C bond might be involved.…”
Section: Resorufin-alcohols (Ref [54])supporting
confidence: 86%
“…The equilibrium constant in the ground state has been estimated to be 1.86 and the hydrogen-bond formation time and the lifetime of hydrogen bond have been determined to be 65 and 120 ps, respectively. The lifetime is similar to the reported 250 ps lifetime of hydrogen bonds in ethanol oligomers isolated in a non-polar solvent [109], but is much longer than the subpicosecond lifetime reported in pure water [110]. The lack of a strong viscosity dependence of the equilibration time suggested that the bond formation/breaking event was a very local motion that did not involve motion of the center of mass of the solvent molecule or largescale rearrangement of the solvent hydrogen-bond network but, rather, that only a simple rotation around the O--C bond might be involved.…”
Section: Resorufin-alcohols (Ref [54])supporting
confidence: 86%
“…These transient bleaching effects cannot be due to a shift in the dissociation-association equilibrium of the oligomers, since temperature jump studies on the EtOH:CCl 4 system have shown that the response of this equilibrium to temperature changes occurs with a time constant of 240 ps. 10 The observed decay of the bleaching can be explained if the vibrational relaxation takes place by a rapid energy transfer from the O-H stretching coordinate r OH to the hydrogen-bond coordinate r OH•••O . 8,11 The excitation energy exceeds the binding energy of the hydrogen bond, which is ϳ2000 cm Ϫ1 .…”
Section: A Hydrogen-bond Predissociationmentioning
confidence: 99%
“…1 The hydrogen bonds of alcohols in apolar solution have been the subject of numerous infrared spectroscopic studies. [2][3][4][5][6][7][8][9][10][11] The strong influence of hydrogenbond formation on the linear response of the O-H stretching mode of ethanol in apolar solution was established 50 years ago. 2 Since then, the coupling between the O-H stretching mode and the hydrogen bond in alcohol oligomers has been extensively characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling between the O--H stretching mode and the hydrogen bond in alcohol oligomers has been extensively characterized [2,3], but detailed knowledge about the dynamical aspects of this coupling was lacking until recently. Using picosecond infrared pump-probe spectroscopy, Graener, Ye and Laubereau [4][5][6] were the first to reveal that excitation of the OH stretching mode of hydrogen-bonded ethanol results in a fast predissociation of the hydrogen bond, followed by a *Corresponding author. much slower reassociation process [4].…”
Section: Introductionmentioning
confidence: 99%